Gifted hands : the Ben Carson story - Carson, Ben (Zondervan Grand RapidsUS, 1990)
Shows how compassion, faith, humility, hardwork and a mother's love and guidance propelled Carson from a disadvantaged childhood to becoming at age 33, the youngest ever Director of Paediatric Neurosurgery at the world-renowned Johns Hopkins Hospital. Includes episodes from his troubled childhood, as well as snapshots of his ground-breaking surgical exploits, related for non-professional readers.